Open box : Künstlerische und wissenschaftliche Reflexionen des Museumsbegriffs - Fehr, Michael; Bert, Büro; Beyer, Marcel; von Bonin, Wibke; Bormann, Johanna; Clever, Beate; Convents, Ralf; Dutschke, Sabine; Ewers, Martina; Flesche, Uwe; Freudenberger, Erhard; Geimer, Peter; et al. (Köln : Wienand Verlag Köln, 1998)
Arman ; Badura, Michael ; Bert, Büro ; Beuys, Joseph ; Boltanski, Christian ; Bonin, Wibke von ; Brecht, George ; Broodthaers, Marcel ; Buthe, Michael ; Caniaris, Vlassis ; Clever, Beate ; Cornell, Joseph ; Costa, Claudio ; Daly, Norman ; Dimitrijevic, Braco ; Distel, Herbert ; Duchamp, Marcel ; Einscheid, Michaela ; Fehlmann, Heinz-Peter ; Filliou, Robert ; Flesche, Uwe ; Freudenberger, Erhard ; Friedberg, Milton ; Van Geluwe, Johan ; Gerz, Jochen ; GIANOZZO ; Günther, Monika ; Herold, Georg ; Hohmann, Iris ; Jones, Joe ; Jung, Helmut ; Kirkeby, Per ; Kounellis, Jannis ; Lang, Nikolaus ; Liptow, Hilmar ; Manzoni, Piero ; Martinchik, Svetlana ; Stepin, Igor ; Mauermann, Karl-Heinz ; Mucha, Maik ; Neumann, Enno ; O'Olbrich, Uwe NevoigtJürgen ; Oldenburg, Claes ; Oppermann, Anna ; Pitzen, Marianne ; Rheinsberg, Raffael ; Roth, Dieter ; Sandfort, Bernhard ; Schult, HA ; Seid, Dui ; Smithson, Robert ; Seltzer, Andreas ; Ulrichs, Timm ; Valentin, Karl ; de Vries, Herman ; Westermann, Günter ; Wexler, Allen ; Zaugg, Rémy ; Aton, Merit ; Beyer, Marcel ; Borchardt, Albert ; Commerell, George ; Musik, Deckstein ; Elben, Georg ; Edvardsson, Gunnar ; Fritsch, Lutz ; Froese, Dieter ; Hardung, Marcel ; Hesseln, Susanne ; Hammelt, Norbert ; Ilten, Rosa von ; John, Franz ; Kaminsky, Thomas ; Kleeb, Hildegard ; Koerver, Jens-Peter ; Kutscher, Vollrad ; Lauten, Anno ; Lechtenberg, Adolphe ; Lohmann, Julia ; Maly, Valerian ; Marjanov, Wasa ; Marsino, Elke ; Megert, Franziska ; Münks, Franziska ; Naidu, Ann-Kathrin ; Niederberger, Jörg ; Nierhoff, Wout ; Schall, Sabine ; Schappert, Roland ; Schilliger, Klara ; Stiller, Thomas ; Stiller, Wolfgang ; Wagner, Hans-Ulrich
Duits
boek